Business transformation from connectivity to digital: case study “PT. MNO Indonesia” - Fauzan, Itsnanta Muhammad; Ihsan, Amirul; Mahmudi, Farhan Annur; Mubarak, Amirsyah Rayhan; Apriono, Catur (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
The telecommunications industry plays a role in meeting the needs of digital connectivity services to the community, especially in line with the community's need for internet connections which is increasing rapidly. As one of the telecommunications service operators in Indonesia,